1994
DOI: 10.1007/bf02757576
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopant cations in the gelation behaviour of silica sols

Abstract: Gelation times of tetraethyl orthosilicate-derived sols containing selected di-to tetravalent cations as dopants were noted at different temperatures (15"-50"C). An analysis of these data, in conjunction with relevant published information, led to the tentative conclusions that (i) unhydrolyzed cations in bare form linked negatively charged silicate polymers in sols, thereby accelerating galation and (ii) hydrolyzed cations retarded the process by offering molecular size-related hindrance and competition for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The high water situation is obviously an outcome of the vaporization of the pore liquid and migration of the bare cation originally solvated by this liquid to the pore surface [13]. The low water situation, on the other hand, can be caused by the incorporation of the dopant cation into the silicate network, via bridging of oligomers, as suggested by Sanchez and McCormick [14] and Patra and Ganguli [ 15]. Further, the cations at the pore surface can also be better screened by the network oxygens as a result of densification and removal of hydroxyl ions (at 900~ as compared to 500~ and 700~…”
Section: Resultsmentioning
confidence: 94%
“…The high water situation is obviously an outcome of the vaporization of the pore liquid and migration of the bare cation originally solvated by this liquid to the pore surface [13]. The low water situation, on the other hand, can be caused by the incorporation of the dopant cation into the silicate network, via bridging of oligomers, as suggested by Sanchez and McCormick [14] and Patra and Ganguli [ 15]. Further, the cations at the pore surface can also be better screened by the network oxygens as a result of densification and removal of hydroxyl ions (at 900~ as compared to 500~ and 700~…”
Section: Resultsmentioning
confidence: 94%
“…For this reason it may simply replace other Brønsted acids like HCl or HNO 3 commonly used in many sol-gel syntheses [1][2][3]18,21]. However small amounts of Pb(NO 3 ) 2 , do not change significantly the solution pH.…”
Section: Discussionmentioning
confidence: 99%
“…Many transition elements and heavy metals act as catalysts in different reactions [17]. In the literature it has been observed that many ions of different metallic elements [18] especially lead ions [19] may accelerate the gelation process in the acid catalyzed sol-gel transition. The lead ion, then, could play the primary role of catalyst for hydrolysis when introduced in a sol-gel solution without the need for any other catalyst.…”
Section: Introductionmentioning
confidence: 99%